Electrowinning of Nuclear-Grade Zr from Ba2ZrF8–ZrF4 Salt System. Issue 2 (3rd January 2018) - Choi, Jeong-Hun; Han, Seul-Ki; Lee, Young-Jun; Lee, Tae-hyuk; Shim, Moon-Su; Nersisyan, Hayk; Suh, Ho-Young; Lee, Jong-Hyeon
Abstract : The electrowinning of nuclear-grade Zr from a Ba2 ZrF8 –ZrF4 salt system at 780°C was investigated by using a zirconium tube and a copper plate as cathode materials. An equimolar Ba2 ZrF8 + ZrF4 mixture was used as a low-melting-point electrolyte. Here, Ba2 ZrF8 is a single source of zirconium and ZrF4 is an auxiliary product to convert Ba2 ZrF8 into a low-melting-temperature BaZrF6 salt ( T melt = 730°C). The cyclic voltammetry measurement indicated that the reduction of Zr 4+ ions has a two-step character corresponding to the Zr 4+ /Zr 2+ and Zr 2+ / Zr0 transitions. The electrochemical reduction behavior of Zr ions on the zirconium tube (inert cathode) and the copper plate (reactive cathode) was analyzed in terms of deposition time and the phase composition of the deposited layers. The metal deposit obtained on the Zr electrode was a single-phase Zr metal, whereas on the Cu electrode, two layers consisting of Cu–Zr and Zr phases were revealed. The further melting of the as-prepared Zr deposit yielded a nuclear-grade Zr ingot with 99.99% purity.